The book of mother : a novel - Huisman, Violaine, 1979- (Scribner, an imprint of Simon & Schuster, Inc., 2021)
Beautiful and charismatic, Catherine, a.k.a. "Maman," smokes too much, drives too fast, laughs too hard, and loves too extravagantly. During a joyful and chaotic childhood in Paris, her daughter Violaine wouldn't have it any other way. But when Maman is hospitalized after a third divorce and a breakdown, everything changes. As the story of Catherine's own traumatic childhood and adolescence unfolds, the pieces come together to form an indelible portrait of a mother as irresistible as she is impossible, as triumphant as she is transgressive.